PENGGUNAAN MULTIMEDIA DAN KOMUNIKASI PERSUASIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA MELALUI E-LEARNING MADRASAH PADA MATA PELAJARAN FIKIH KELAS XII IPS 3 SEMESTER GANJIL DI MAN 1 GROBOGAN TAHUN PELAJARAN 2020/2021 - Zainudin Aziz; Moh Muthohir (Pixel :Jurnal Ilmiah Komputer Grafis, 2020)
This research was motivated by learning activities forced by circumstances (during the Covid-19 pandemic) to change from face-to-face to virtual face-to-face. This raises a separate problem to immediately find an alternative solution. The purpose of this study was to obtain data about the description of the implementation of persuasive communication activities in order to improve student learning outcomes through E-Learning Madrasah’s in fiqh class XII IPS 3 Odd Semester at MAN 1 Grobogan. The research method used was Classroom Action Research (PTK). The research was carried out in two cycles, each cycle consisting of planning, action, observation, and reflection. The subject of this research was carried out in class XII IPS 3 MAN 1 Grobogan, totaling 35 students. The data collection used in this research is qualitative and quantitative data. The results of this study indicate that the use of persuasive communication through Madrasah E-Learning conducted to students of class XII IPS 3 MAN 1 Grobogan, can improve student learning outcomes. This can be shown by the average test results of student learning in the first cycle of 77 with the total class completeness of 71.4%. Then the average value of student learning outcomes increased to 88 with the total class completeness of 91.4% in cycle II